Digital Scholarly Editing : Theories and Practices (2009)
The NeDiMAH Experts’ Seminar on Digital Scholarly Editions, held at the Huygens Institute for the History of the Netherlands in The Hague in November 2012, was one of the most substantial and concentrated gatherings around a given subject I have ever, I think, attended. Nor is this an idealised memory: it is now fully borne out by the essays deriving from that Seminar assembled in the present volume, each of which is a fresh and much deepened take on the topics addressed in The Hague.